Use of a Comic Book to Assist Pharmacy Student Learning of the Affordable Care Act (ACA) - Jagannath Muzumdar; Somnath Pal (University of Minnesota Libraries Publishing, 2018)
Purpose:  To assess the pedagogical effectiveness of a comic book in pharmacy student learning of the Affordable Care Act (ACA).   Methods: Comparative-group, matched pre-posttest survey design was used to measure pharmacy students' comprehension of ACA. PharmD students (P-1year) from two sections of a Pharmacy and US Healthcare course participated in this study. Treatment group students received a comic book on ACA. The comparison group received the textual information, without pictures, from the book in a typed document. A posttest survey was administered later in the semester, before the instructor discussed ACA in class. Fourteen questions, developed from the information in the book and document, assessed pharmacy students' comprehension of ACA. Response options included a visual analogue scale. Independent sample t-test was used to assess the differences in the mean pre-posttest scores between the two groups. Results: A total of 103 (n = 49 comparison vs. n = 54 treatment group) students completed the survey. No statistically significant differences were found in the pre-test mean scores between the groups. Differences in the pre-post test mean scores of treatment group were significantly higher than the differences in the mean scores of the comparison group. Students agreed that the comic book format gave them a better understanding of ACA and increased their interest in learning more about the Act.  Conclusion: Comic books were found to be effective in student learning of the ACA. The positive response from students highlight the point that pharmacy faculty could use comic books as supplemental reading in pharmacy courses.   Conflict of Interest This research was made possible through the faculty start-up funds awarded by the College of Pharmacy and Health Sciences, St. John's University. Treatment of Human Subjects: IRB review/approval required and obtained Type: Original Research